PSYCHOLOGICAL ASSESSMENT THROUGH VARIOUS TESTS: A CASE STUDY OF 11-YEAR-OLD GIRL EXPERIENCING BRIEF PSYCHOTIC DISORDER WITH MARKED STRESSORSORDER WITH MARKED STRESSOR (The Research of Medical Science Review, 2025)
This is a case of 11-year-old girl in grade 4. She was referred for psychological assessment and intervention due to significant emotional and behavioural issues. Her symptoms include intense jealousy, hypnagogic and visual hallucinations, irritability, and occasional physical aggression towards peers and cousins. She experiences perceptual disturbances, such as seeing distorted faces and objects, which cause fear and emotional distress. These challenges have led to anxiety regarding her school performance, social relationships, and overall emotional regulation, further exacerbating her struggles. Various psychological constructs were used to analyses these symptoms, such as BDI-II, CPM (Colored Progressive Matrices), RCADS, and HTP. CBT was considered effective, alongside medication, to work on her dysfunctional thoughts. Token Economy (a technique of behavioral therapy) was utilized for behavioral activation. In addition, ABA Therapy and Star Chat therapy were also found to be helpful.